OPUS DEI: BEYOND THE FICTION - Hidayatullah, Abi Makarim; Purnomosasi, Lusia Kristiasih Dwi (English Teaching Journal, 2014)
The purpose of this research is to describe the Opus Dei organization inside The Da Vinci Code movie and Opus Dei in reality. It is due to the controversies and much efforts to defend the truth against Â the Â movie. Â This Â research Â uses Â descriptiveÂ qualitative Â method. Â TheÂ researcher Â needs Â a sociology of literature by Alan Swingewood to get evidences the effect and goals of the author in creating a story. The analysis reveals that the representation of Opus Dei inside The Da Vinci Code confirms as dangerousÂ organization, destructive mission, a killer, and corrupted members.Â It is contradiction facts far from reality that Opus Dei concerns on the serving people to keep devotion of Christian. Opus Dei is the open legal organization doing charity for better living which has mission and independent finance sources. The conclusion show that the controversies functions to get the movieâs rating raised since it deals with the mass demand in popular literature. The evidences confirm that the representation of Opus Dei inside The Da Vinci Code are negated from the reality.